Thunderball - Young, Terence; Celi, Adolfo, 1922-1986.; Claudine Auge; Guy Doleman; Luciana Paluzzi; Molly Peters; Rik Van Nutter; Sean Connery (UK, USA Danjaq, 1965)
SPECTRE hatches its most audacious plot to date when its agents hijack a British Vulcan bomber armed with two atomic bombs and hold NATO to ransom for the sum of #100,000,000. The British send all their ""00"" agents, including James Bond, to recover the warheads before SPECTRE carries out its threat to detonate the devices on the UK and US mainlands.
When SPECTRE steals two nuclear bombs for a massive extortion scheme, agent 007 is sent in to find them before they can be used.
Kevin McClory
Language(s): English
Subtitle(s): English, Turkish
Keywords: Adventure; Thriller; Action